Home free [large type] - Michaels, Fern (Michaels, Fern. Sisterhood, 2011)
President Martine Connor, the Sisterhood's long-time ally, has announced the formation of a top-secret organization. Officially, the CIC won't exist. Unofficially, they'll report directly to the president and tackle the jobs no one else can handle. For the Sisterhood, it's the end of an era--and the beginning of a whole new adventure.